Spatiotemporal Dynamics of Vibrio Communities and Abundance in Dongshan Bay, South of China - Xu, Wei; Gong, LinFeng; Yang, Shuai; Gao, Yuanhao; Ma, Xiaowan; Xu, Limei; Chen, Haisheng; Luo, Zhuhua (Frontiers in Microbiology, 2020)
Vibrio genus inhabit estuarine and marine ecosystem throughout the world and can cause severe infections in humans and animals. Previous studies have demonstrated the dynamics of Vibrio at both community and population levels and to assess the close relationship between environmental factors and Vibrio diversity and abundance, such as temperature, salinity, and dissolved oxygen. It is also generally believed that aquaculture is the fastest-growing food sector, which also applying great environmental impacts on microbial communities in aquatic ecosystems. However, our understanding of the spatio-temporal quantification of Vibrio throughout the four seasons in the aquaculture zone and response to environmental factors remains poor. To explore the spatiotemporal distribution and abundance of the Vibrio community with their related environmental factors and detect the relationships among them, we collected 10 seawater sites spanning four seasons across the whole year in Dongshan Bay for investigating the Vibrio community dynamics. Marked differences in diversity and abundance of the Vibrio community were observed between seasons, which were mainly driven by temperature, dissolved oxygen, nitrate, and nitrite. qPCR analysis showed that Vibrio abundance was most abundant in the Summer (5.37× 106 copies/L), compared to the autumn (4.58×106 copies/L), spring (1.18×106 copies/L) and winter (1.55×104 copies/L). A total of 22 Vibrio OTUs and 28 species were identified by universal bacteria 16S rRNA gene and cultivation methods, with Vibrio fortis were dominant in these aquaculture areas. To summarize, our presents study is one of the few studies to research the occurrence of Vibrio in marine aquaculture of South China, and the results indicate that Vibrio are widely distributed in aquaculture environment and a further risk assessment is needed to conduct.